2010
DOI: 10.1186/1465-9921-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Altered fibroblast proteoglycan production in COPD

Abstract: BackgroundAirway remodeling in COPD includes reorganization of the extracellular matrix. Proteoglycans play a crucial role in this process as regulators of the integrity of the extracellular matrix. Altered proteoglycan immunostaining has been demonstrated in COPD lungs and this has been suggested to contribute to the pathogenesis. The major cell type responsible for production and maintenance of ECM constituents, such as proteoglycans, are fibroblasts. Interestingly, it has been proposed that central airways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 37 publications
(45 reference statements)
10
97
1
Order By: Relevance
“…The donor lungs from the healthy individuals had been judged by the clinicians to be suitable for lung transplantation and we received the lungs due to the fact that they could not find any matching recipients at the moment. Despite the limited numbers of observations in the present study, we could support the findings in our other studies (21,22) that the different sampling techniques and the age distribution in the two study control populations did not interfere with the obtained results. However, it would be plausible to have lung function data and exhaled NO levels from all the controls, i.e.…”
Section: Proteoglycan Syntheses Are Closely Regulated By Different Masupporting
confidence: 78%
See 1 more Smart Citation
“…The donor lungs from the healthy individuals had been judged by the clinicians to be suitable for lung transplantation and we received the lungs due to the fact that they could not find any matching recipients at the moment. Despite the limited numbers of observations in the present study, we could support the findings in our other studies (21,22) that the different sampling techniques and the age distribution in the two study control populations did not interfere with the obtained results. However, it would be plausible to have lung function data and exhaled NO levels from all the controls, i.e.…”
Section: Proteoglycan Syntheses Are Closely Regulated By Different Masupporting
confidence: 78%
“…Some control lung fibroblasts (n=3) were instead isolated from lung explants from unused donors meant for lung transplantation (21). Importantly, alveolar parenchymal specimens from lung explants were collected 2-3 cm from the pleura in the lower lobes, equivalent to the location where the transbronchial biopsies were obtained.…”
Section: Collection Of Transbronchial Biopsies and Fibroblast Culturesmentioning
confidence: 99%
“…hPF were used to model effects that could occur in lungs following inhalation of EC refill fluid vapors. It is well established that conventional cigarette products can effect lung fibroblasts and lead to disease development (Hallgren et al, 2010;Selman and Pardo, 2002;Kitamura et al, 2011;Togo et al, 2008). These cell types were also used in our prior study (Bahl et al, 2012) and therefore allow comparison to prior our work and to planned future work involving aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in versican in the parenchyma of COPD lung, and its ability to block formation of elastic fibers may explain why restoration of a functional elastic fiber network does not occur in lungs affected by COPD or in other emphysematous diseases . It has also been reported that versican production is higher in lung fibroblast cells isolated from COPD patients (GOLD stage ), consistent with the lack of elastic fiber repair and a negative influence on the elastic recoil, and suggesting that the relationship exists in patients with severe COPD (Hallgren et al, 2010). A caveat to this proposed relationship, however, is that lower levels of versican have been reported in distal parenchyma of COPD patients compared with nonsmokers and non-obstructed smokers even though elastic fiber fractional areas are also low (Annoni et al, 2012).…”
Section: Versican Knockdown Restores Cse-related Loss Of Insoluble Elmentioning
confidence: 62%